The Reality behind Informal Health Payments in Iran: "Under the Table Payments" or "On the Table Payments"? - Mohammad MESKARPOUR-AMIRI; Abbas ASSARI-ARANI; Hosein SADEGHI; Lotfali AGHELI (Tehran University of Medical Sciences, 2017)
The Reality behind Informal Health Payments in Iran: "Under the Table Payments" or "On the Table Payments"?